Intelligent computer mathematics : MKM, Calculemus, DML, and Systems and Projects 2013, Held as Part of CICM 2013, Bath, UK, July 8-12, 2013. Proceedings - Aspinall, David; Lange, Christoph; Sojka, Petr; Windsteiger, Wolfgang; Carette, Jacques (Lecture Notes in Computer Science, 2013)
This book constitutes the joint refereed proceedings of the 20th Symposium on the Integration of Symbolic Computation and Mechanized Reasoning, Calculemus 2013, 6th International Workshop on Digital Mathematics Libraries, DML 2013, Systems and Projects, held in Bath, UK as part of  CICM 2013, the Conferences on Intelligent Computer Mathematics. The 7 revised full papers out of 18 submissions for MKM 2013, 5 revised full papers out of 12 submissions for Calculemus 2013,  6 revised full papers out of 8 submissions for DML 2013, and 12 revised full papers out of 16 submissions for Systems and Project track presented together with 3 invited talks were carefully reviewed and selected, resulting in 33 papers from a total of 73 submissions.